The influence of Islamic leadership style and work ethic on employee performance in Salamrejo Village, Binangun District, Blitar Regency - Sutowo Sutowo; Abdul Aziz Al Kaharudin; Yusada Andri Hermawan (Priviet Social Sciences Journal, 2025)
This study aimed to examine the influence of the Islamic leadership approach and Islamic labor ethic on workers' performance within the Salamrejo Village Office, Binangun District, Blitar Regency. The problem formulations proposed include: (1) how does Islamic leadership style influence employee performance, (2) how does the Islamic approach to work influence worker performance, and (3) how do Islamic leadership style and Islamic work ethic influence employee performance simultaneously. This study uses a quantitative approach with a descriptive-verification design. Data collection was performed by distributing Likert-scale-based questionnaires to the entire village employee population using a saturated sampling method. Data analysis included validity, reliability, normality, heteroscedasticity tests, and hypothesis testing using the t-test (partial) and F-test (simultaneous) with the help of the SPSS software. The results showed that all research instruments were valid and reliable (Cronbach's Alpha X1 = 0.689; X2 = 0.855; Y = 0.852). The data were normally distributed (Asymp. Sig = 0.057 > 0.05) and free from heteroscedasticity. The t-test showed that Islamic leadership style had a significant positive effect on employee performance (t = 6.010; sig < 0.001), while the Islamic approach to work had a significant negative impact on worker performance (t = -2.859; sig = 0.024). Simultaneously, both independent variables significantly impacted worker performance (F = 20.513; sig = 0.001). Thus, this study concluded that Islamic leadership style is a dominant factor in improving employee performance, while the implementation of Islamic work ethic requires further evaluation to align with work values ​​and contribute optimally to improving performance.